Clinical implications of low estimated protein intake in patients with heart failure. Issue 3 (14th April 2022) - Streng, Koen W.; Hillege, Hans L.; ter Maaten, Jozine M.; van Veldhuisen, Dirk J.; Dickstein, Kenneth; Ng, Leong L.; Samani, Nilesh J.; Metra, Marco; Ponikowski, Piotr; Cleland, John G.; Anker, Stefan D.; Romaine, Simon P.R.; et al.
Abstract: Background: A higher protein intake has been associated with a higher muscle mass and lower mortality rates in the general population, but data about protein intake and survival in patients with heart failure (HF) are lacking. Methods: We studied the prevalence, predictors, and clinical outcome of estimated protein intake in 2516 patients from the BIOlogy Study to TAilored Treatment in Chronic Heart Failure (BIOSTAT‐CHF) index cohort. Protein intake was calculated in spot urine samples using a validated formula [13.9 + 0.907 * body mass index (BMI) (kg/m 2 ) + 0.0305 * urinary urea nitrogen level (mg/dL)]. Association with mortality was assessed using multivariable Cox regression models. All findings were validated in an independent cohort. Results: We included 2282 HF patients (mean age 68 ± 12 years and 27% female). Lower estimated protein intake in HF patients was associated with a lower BMI, but with more signs of congestion. Mortality rate in the lowest quartile was 32%, compared with 18% in the highest quartile ( P < 0.001). In a multivariable model, lower estimated protein intake was associated with a higher risk of death compared with the highest quartile [hazard ratio (HR) 1.50; 95% confidence interval (CI) 1.03–2.18, P = 0.036 for the lowest quartile and HR 1.46; 95% CI 1.00–2.18, P = 0.049 for the second quartile]. Conclusions: An estimated lower protein intake was associated with a lower BMI, but signs of congestion were more prevalent. A lower estimated protein intake was independently associated with a higher mortality risk.